The Relationship Between Hair Zinc Levels, Feeding Patterns, and Infectious Diseases on The Incidence of Stunting in Children Aged 24-59 Months in The City of North Jakarta, Province of DKI Jakarta - Febriana Ramadhani Fitry; Ani Margawati; Ahmad Syauqy; Muflihatul Muniroh; Apoina Kartini (Green Publisher Indonesia, 2024)
Globally, stunting is a severe public health concern, especially in low- and middle-income nations like Indonesia. It is typified by stunted growth and development due to recurrent infections and chronic malnutrition. North Jakarta has a 19.8% stunting incidence, according to the 2023 Indonesian Health Survey. This indicates the critical need for additional research into the factors contributing to stunting, such as hair zinc levels, dietary habits, and infectious infections. This study employs an observational case-control design conducted in North Jakarta in March 2024. Stunting incidence and hair zinc levels are significantly correlated (p=0.000), affecting 87.5% of children with low hair zinc levels. Stunting is also correlated considerably (p=0.000) with incorrect feeding patterns; 75.7% of children who exhibit these patterns are stunted. On the other hand, there was no statistically significant correlation (p=0.806) between the incidence of stunting and a history of infectious illnesses. The mother's level of education, the child's age, gender, and family income did not significantly correlate with stunting.